BIOPESTICIDAL ACTIVITY OF Calotropis procera L. AGAINST Macrophomina phaseolina - Waheed, Nidra; Jabeen, Khajista; Iqbal, Sumera; Javaid, Arshad (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Mungbean [Vigna radiata (L.) Wilczek] is an important pulse crop globally. This imperative crop is severely affected by charcoal rot disease caused by Macrophomina phaseolina (Tassi) Goid. In the present study, the leaves of Calotropis procera L. were tested for their antifungal potential against M. phaseolina. Materials and Methods: Various concentrations i.e. 1%, 2.5%, 4%, 5.5% and 7% of methanolic extract of C. procera leaves were prepared and their in vitro bioactivity was examined against the test fungus. Methnolic leaf extract was partitioned using n-hexane, chloroform, ethyl acetate and n-butanol and antifungal activity of each fraction was evaluated. n-Hexane fraction was subjected to GC-MS analysis. Results: The higher concentration of methanolic leaf extract (7%) caused maximum inhibition in the diameter of M. phaseolina i.e. 38%. The n-hexane fraction of methanolic leaf extract was found to be the most effective against M. phaseolina. Seven compounds belonging to classes of chlorocarbon, aromatic hydrocarbon, azocompounds, aromatic carboxylic acids and fatty acids were identified in GC-MS analysis of n-hexane fraction. Conclusion: Antifungal activity of the methanolic leaf extract of C. procera might be due to the presence of the identified compounds in n-hexane fraction of methanolic leaf extract.